KADAR DEBU DAN KELUHAN PERNAFASAN TENAGA KERJA (Studi Kasus Pada Tenaga Kerja di Gudang dan Penyortiran Bahan Baku Produksi Tali Rfia PT. Hobab Perkasa di Jombang) - Anjar Pra Setyaningati; Musta'in .; Erna Triastuti (GEMA LINGKUNGAN KESEHATAN, 2013)
Impacts of dust exposure may disturb working enjoymeny and in longer priod may causedisturbances on respiratory passages and pulmonary functions. In addition to dust exposure,respiratory complaints may be caused by other factors relating to the workers, such as age,length of occupation that may explain how long was a worker was exposed to dust, smokinghabit and their habit in wearing protective masks to protect their respiration. The purposes ofthis research was to describe level of dust concentration and complaints relating to workers'respiration. The study also engaged in the assessment of controlling efforts that includetechnical, administrative controls and the use self-protective devicesThis was a descriptive study using a cross sectional approach. Data collection was doneby observation, interviews and measurements. Population under study was the entire workerswho worked at warehouses and raw material sorting division. The number of the sample wasthe total of population of workers that amounted to 30 workers. Data were analyzeddescriptively using cross tabulation which explained the object under study.Result of the study indicated that the dust level measured from 30 samples was incompliance to the TLV (57%) that was 0.15 mg/m3 • Most of workers (63%) aged ~ 40 yearsold. Most of workers (63%) have smoking habit. Most of worker (93%) did not wear maskswhile working. Most of the workers (60%) have moderate complaint. The efforts in controllingthe issue was not satisfactory. Respiration complaints more likely associated to length ofoccupation, smoking habit, and utilization of protective masks.The study suggested to install Local Exhaust Ventilation to reduce dust level in theworkplace; the company was encouraged to make cooperation with related institutions inconducting OSH or K3 training, and the company should give rigid penalties against workerswho wear their PPD reluctantly.Keywords : Dust level, respiration complaint, Hobab Perkasa